The Effect of Prior Knowledge and ASSURE Model on Simulation and Digital Communication Learning Outcomes in Vocational High School - Yudha Aditya Fiandra; Nizwardi Jalinus; Ridwan Ridwan; Rijal Abdullah (Jurnal VARIDIKA, 2022)
This research is in the form of experimental research. The purpose of this study was to examine and see the effect of applying the ASSURE model and prior knowledge on the results of Simulation and Digital Communication subjects at the SMK. The population involved in this study were students majoring in Computer and Network Engineering class X SMKN 3 Pariaman, where class A was the experimental class and class B was the control class. These two classes were also divided into two groups, high and low prior knowledge. This study uses a 2x2 factorial design. Hypothesis testing using two-way ANOVA test. The results obtained are that (1) the learning model has a significant effect on learning outcomes, the ASSURE model gets a higher score than the conventional learning model, (2) prior knowledge has a significant effect on learning outcomes, higher prior knowledge gets a higher score than the conventional learning model. which is low, and (3) there is no interaction between the learning model and prior knowledge on learning outcomes. The N-Gain test showed that high prior knowledge in the ASSURE learning model got the highest improvement results and low prior knowledge from conventional classes got the lowest results.